2016
DOI: 10.1371/journal.pone.0164772
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Malnutrition among Guatemalan Children at 2 Years of Age

Abstract: ObjectiveTo identify the prevalence and predictors of malnutrition among 2-year old children in the Western Highlands of Guatemala.MethodsProspective cohort of 852 Guatemalan children in San Lucas Toliman, Guatemala followed from birth to age 2 from May 2008 to December 2013. Socio-demographic, anthropometric, and health data of children was collected at 2 month intervals.ResultsAmong the 402 males and 450 females in the cohort, mean weight-for-age Z-score (WAZ) declined from -0.67 ± 1.01 at 1 year to -1.07 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These findings were confirmed by other studies, where they also found that male children were significantly more likely to suffer from stunting. 17,22,41 The reason for this gender divergence is not well established, but it is believed that boys are more influenced by environmental stress than girls. 42 Our study also demonstrated that maternal education was a significant positive factor for controlling childhood stunting, and a child from a higher-educated mother suffers less, and findings are in line with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were confirmed by other studies, where they also found that male children were significantly more likely to suffer from stunting. 17,22,41 The reason for this gender divergence is not well established, but it is believed that boys are more influenced by environmental stress than girls. 42 Our study also demonstrated that maternal education was a significant positive factor for controlling childhood stunting, and a child from a higher-educated mother suffers less, and findings are in line with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have identified different socioeconomic and maternal factors that are strongly associated with different forms of undernutrition (ie, stunting, wasting, and underweight). [5][6][7][8]28,29 Based on the published literature, a number of explanatory variables, such as age and sex of the children, maternal age, education, access to electronic media, residence, and socioeconomic status, were included in the decomposition analysis. Maternal education was categorized as no education, primary level of education, and secondary and higher secondary level of education.…”
Section: Major Explanatory Variablesmentioning
confidence: 99%
“…However, socioeconomic inequity because of undernutrition has become a critical concern as such inequity is present throughout the developing world . Several studies have documented that children from richer families and living in urban areas are better‐off in terms of nutritional indicators than their poorer and rural counterparts . In addition, urban‐rural disparities continue to exist in education, economic status, employment opportunity, and other sociocultural dimensions that have a significant impact on child health .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that there was association between vomiting and malnutrition, 58.7% of malnourished children had vomiting. Nagata‫‬ et al showed that vomiting and WAZ at 1 year were significant predictors of undernutrition at 2 years [22] . Although, Sermet-Gaudelus et al in 2000) showed that vomiting was not significant predictors of undernutrition [23] .…”
Section: "Gomez Classification Of Malnutrition"mentioning
confidence: 99%